Working group n° 2: women and rural development - Navarra V.; Sagardoy J.A. (Women status in the Mediterranean: their rights and sustainable development, 2009)
Rural development, analyzed in a gender perspective, should focus on the setting up and enforcement of the institutions especially involved in development. This is aimed to: (i) facilitate women access to training and information; (ii) create new job opportunities expressly addressed to women and youth people; (iii) develop the relationship between agriculture and the other economic sectors.
International Meeting on Women Status in the Mediterranean: their Rights and Sustainable Development, 2008/06/16-17, Bari (Italy)